Development of pH-responsive nanoparticles for the protection and delivery of RNAs to cancer cells - Graça, Tiago Samuel Silva (2024)
Nanoparticles are receiving increased attention due to their significance in delivering biopharmaceuticals for gene-based therapies. At the same time, RNA is being studied to develop new and advanced treatments. However, the successful therapeutic application of these biomolecules is highly dependent on their effectiveness in reaching target cells. The development of pH-responsive nanoparticles may improve delivery efficiency in certain diseases that present a microenvironment with deregulated pH, such as lung cancer. In this work, it is explored the pH responsiveness and efficiency of a copolymer composed of poly(2- (diisopropylamino)ethyl methacrylate)) (PDPA) and poly(oligo(ethylene oxide)methyl ether methacrylate) (POEOMA) for the encapsulation and release of small RNAs (sRNA). The encapsulation process relies on the electrostatic interaction between the negatively charged sRNA and the protonated tertiary amine groups of the PDPA segment. Three copolymers with different architectures (linear or 4-arm star-shaped) and compositions (4-arm star PDPA-b-POEOMA or 4-arm star POEOMA-b-PDPA) were synthesized by atom transfer radical polymerization. The sRNA and miR-29b-duplex encapsulation efficiencies were studied by UV spectroscopy and agarose electrophoresis. The best formulations were further characterized regarding the size and surface charge of the polyplexes, by dynamic Light Scattering (DLS) and electrophoretic Light Scattering (ELS), respectively. Depending on the copolymer, concentration, and pH of the formulation, the systems achieved complexation efficiencies ranging from 35% to 84%. The polyplexes presenting higher encapsulation efficiencies had sizes ranging from 92 to 104 nm. It was also possible to understand the changes in the nanoparticle’s structure at different pH values with TEM, which are in accordance with their release potential and profile, studied by UV spectroscopy and confirmed by agarose electrophoresis. Additionally, the nanoparticles of the different conformations were submitted to several biologically relevant conditions to evaluate their protection capacity, where the 4-arm star, POEOMA core, and copolymer proved to have superior properties than their linear and conformational inverse counterparts. Moreover, cell viability, via MTS assays was employed where all three architectures proved biocompatible. This research demonstrates the potential of pH-sensitive polymers as promising RNA delivery systems, and how the different conformations inside the same copolymer block combination can influence its overall performance as an effective delivery vehicle.